Impact of Embedded Pipe Configuration in Phase Change Material on Photovoltaic Cooling - Diana, Lohdy; Aziz, Abdul; Safitra, Arrad Ghani; Pratilastiarso, Joke; Kusumawati, Eny (Journal of Mechanical Engineering, Science, and Innovation, 2025)
The photovoltaic as a solar power plant is increasingly widespread as renewable energy. However, high photovoltaic surface temperatures can reduce performance in generating electricity. Based on these problems, a photovoltaic cooling system is needed. This research aims to produce effective photovoltaic cooling by planting pipes that carry cold fluid embedded in Phase Change Material. The experimental research used solar simulator, there are three variations of pipe configuration, including: parallel, serpentine, and circular. The photovoltaic used in this research has a specification of 50WP. This study examines the effect of various cooling pipe configurations on thermal performance, output power, and the reduction of photovoltaic temperature. The results show the serpentine pipe configuration exhibits the highest thermal efficiency initially but declines drastically over time, while the circular pipe design demonstrates the best long-term stability and efficiency. Specifically, the circular pipe variation effectively reduces the photovoltaic surface temperature, maintaining the lowest temperature of around 42°C at the 80th minute, compared to higher peak temperatures in the unmodified variation 67°C, serpentine 50°C, and parallel 45°C. Overall, the circular pipe design is identified as the most effective cooling method for maintaining low surface temperatures and ensuring stable performance in photovoltaic panels.